Chromogenic anti-FXa assay calibrated with low molecular weight heparin in patients treated with rivaroxaban and apixaban : possibilities and limitations - Margetić, Sandra (Array, 2020)
Clinical application of rivaroxaban and apixaban does not require therapeutic monitoring. Commercial anti-activated factor X (anti-FXa) inhibition methods for all anti-FXa drugs are based on the same principle, so there are attempts to evaluate potential clinical application of heparin-calibrated anti-FXa assay as an alternative method for direct FXa inhibitors. We aimed to evaluate relationship between anti-FXa methods calibrated with low molecular weight heparin (LMWH) and with drug specific calibrators, and to determine whether commercial LMWH anti-FXa assay can be used to exclude the presence of clinically relevant concentrations of rivaroxaban and apixaban. Materials and methods: Low molecular weight heparin calibrated reagent (Siemens Healthineers, Marburg, Germany) was used for anti-FXa activity measurement. Innovance heparin (Siemens Healthineers, Marburg, Germany) calibrated with rivaroxaban and apixaban calibrators (Hyphen BioMed, Neuville-sur-Oise, France) was used for quantitative determination of FXa inhibitors. Results: Analysis showed good agreement between LMWH calibrated and rivaroxaban calibrated activity (κ = 0.76) and very good agreement with apixaban calibrated anti-Xa activity (κ = 0.82), respectively. Low molecular weight heparin anti-FXa activity cut-off values of 0.05 IU/mL and 0.1 IU/mL are suitable for excluding the presence of clinically relevant concentrations (<30 ng/mL) of rivaroxaban and apixaban, respectively. Concentrations above 300 ng/mL exceeded upper measurement range for LMWH anti-FXa assay and cannot be determined by this method. Conclusion: Low molecular weight heparin anti-FXa assay can be used in emergency clinical conditions for ruling out the presence of clinically relevant concentrations of rivaroxaban and apixaban. However, use of LMWH anti-FXa assay is not appropriate for their quantitative determination as an interchangeable method.